1989
DOI: 10.1111/j.2044-8279.1989.tb03088.x
|View full text |Cite
|
Sign up to set email alerts
|

The Transition From Single‐sex to Co‐educational High Schools: Teacher Perceptions, Academic Achievement, and Self‐concept

Abstract: SUMMARY.The purpose of this paper is to summarise a five-year longitudinal study of the effects of the transition from single-sex high schools to co-educational high schools. During this period two single-sex high schools serving the same geographical area formed two co-educational high schools. The results of the present investigation are presented in three parts: (1) the impact of the transition from the perspective of teachers and staff who taught at the schools before, during, and after the transition; (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
13
0
2
Order By: Relevance
“…We observed no family background differences between students as observed in Grade 8 or Grade 10, and this appears to confirm Lee and Bryk's (1989) speculation that single-sex and coeducational Catholic schools enroll roughly the same sorts of students. However, because Lee and Bryk (1986) and others (Riordan, 1985(Riordan, , 1990Marsh, 1989) who used the HS&B data did find sector differences in family background as measured in Grade 10 and because we did not, we are left to wonder whether something about Catholic schools has changed between 1980 and 1990. In any case, we are unable to say whether users of HS&B would have observed no sector differences in students' family backgrounds had they been able to observe students in Grade 8, and our data do little to clear up the matter.…”
Section: Educational Aspirations In Gradementioning
confidence: 68%
See 2 more Smart Citations
“…We observed no family background differences between students as observed in Grade 8 or Grade 10, and this appears to confirm Lee and Bryk's (1989) speculation that single-sex and coeducational Catholic schools enroll roughly the same sorts of students. However, because Lee and Bryk (1986) and others (Riordan, 1985(Riordan, , 1990Marsh, 1989) who used the HS&B data did find sector differences in family background as measured in Grade 10 and because we did not, we are left to wonder whether something about Catholic schools has changed between 1980 and 1990. In any case, we are unable to say whether users of HS&B would have observed no sector differences in students' family backgrounds had they been able to observe students in Grade 8, and our data do little to clear up the matter.…”
Section: Educational Aspirations In Gradementioning
confidence: 68%
“…Indeed, as Lee and Bryk (1986) and others (Riordan, 1985(Riordan, , 1990 have concluded, students in single-sex secondary Catholic schools take more academically oriented courses, score higher on standardized achievement tests, and have higher educational aspirations. On the other hand, advocates of coeducational schooling have cast doubt on the differential effectiveness of single-sex and coeducational schooling, arguing that single-sex schools are no more advantageous, either academically or socially, than coeducational schools (Dale, 1974;Dale & Miller, 1972;Marsh, 1989aMarsh, , 1989bMarsh, , 1991Marsh, Owens, Myers, & Smith, 1989).…”
Section: Arguments For and Against Coeducationmentioning
confidence: 98%
See 1 more Smart Citation
“…There is a debate between advocates of single sex education (Jimenez & Lockheed, 1989;Lee & Bryk, 1986Lee & Marks, 1990;Mael, 1998), and advocates of coeducation (Dale, 1974;Marsh, Owens, Myers, & Smith, 1989;Schneider & Coutts, 1982). Many researchers have found that girls in single-sex schools performed better than their coeducational school counterparts (Baker, 2002;Jimenez & Lockheed, 1989;Lee & Marks, 1990;Mael, 1998).…”
Section: Single-sex Vs Coeducationmentioning
confidence: 99%
“…12 Motivacija ima v mladostništvu zelo veliko vlogo predvsem v okviru učenja in izobraževanja, saj skrb za šolo in učno uspešnost že v zgodnjem mladostništvu postaja pomemben dejavnik pri načrtovanju mladostnikovega nadaljnjega izobraževanja, ki začrta tudi njegovo kasnejšo poklicno kariero (Anderman in Maehr, 1994). Raziskave kažejo, da se z vstopom v mladostništvo občutno zmanjšajo trije pomembni dejavniki učne uspešnosti: stališča do šole, samopodoba, ki se nanaša na sposobnosti, in motivacija učencev (Epstein in McPartland, 1976;Harter, 1981;Marsh, Owens, Myers in Smith, 1989). Anderman in Maehr (1994) predpostavljata tri možne individualne vzroke upada motivacije v mladostništvu: (i) razvojne spremembe, (ii) spremembe v samopodobi, ki deluje kot motivator, in (iii) prehodi med notranjo in zunanjo motivacijo; z njimi pa se prepletajo tudi spremembe v ožjem in širšem socialnem okolju, v katerem živi mladostnik.…”
Section: Notranji In Zunanji Motivacijski Viriunclassified